If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(h + 11) = 0 Reorder the terms: 7(11 + h) = 0 (11 * 7 + h * 7) = 0 (77 + 7h) = 0 Solving 77 + 7h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-77' to each side of the equation. 77 + -77 + 7h = 0 + -77 Combine like terms: 77 + -77 = 0 0 + 7h = 0 + -77 7h = 0 + -77 Combine like terms: 0 + -77 = -77 7h = -77 Divide each side by '7'. h = -11 Simplifying h = -11
| 12x-13=-35-5x | | x=2x^2-3x-4 | | y-8=-2(x+7) | | y-8=2(x+7) | | 3u-2=u-5w | | 6p^2+8p-1=0 | | 3x-5x-6=2x-4 | | 7-3x=6x+1 | | 3(4p+7)=3(7p+6) | | (2b+5)(a-4)=0 | | -(6p+4)= | | 6y+10=16 | | 9+5j=4j | | 5n-7=6n | | ln(x-1)=3lnx | | x*x+13=17 | | -2.8(x+4.9)=18.6 | | https://content.thinkthroughmath.com/uploads/image/image/498850/G34L315Q1041S-e76a60e86a99e0ee99c586c66277fdce-2ebf43d22addc42099f0886cc04e9e34.png | | (-7+11)(-12x+3)= | | -7(1-x)=49 | | x+(x-12)=38 | | 2(4w-6)= | | 3x+5(6x-8)=2 | | 9x*x-25=0 | | 2/4=v/6 | | -5(4p-2)= | | -3/n | | 18x*x+15x-12=0 | | 3(3+5)=12 | | C(t)=t^2-10+110 | | -3m-6=12 | | 3r-42=21 |